Enhancing early childhood creativity through loose-parts media based on STEAM learning - Dewi, Ayu Citra; Alif Laini; Sri Intan Wahyuni; Mega Cahya Dwi Lestari (Aṭfālunā Journal of Islamic Early Childhood Education, 2024)
This article examines classroom action research in which researchers and classroom teachers collaborate to understand and improve the benefits of loose-part media to increase children's creativity and the subsequent impact of loose-part media based on STEAM learning. Focusing on early childhood education, this research was carried out in collaboration with teachers provided 21 pupils 5–6-year-old at Mutiara Kasih Kindergarten in Padang City. The research procedures carried out included a combination of observation, discussion and reflection on practice in 3 cycles. Loose-part media based on STEAM learning is considered to have increased children's creativity, as shown by pre-cycle data of 6.9%. Cycle I was carried out with a creativity percentage of 15.4%, increasing to 47.1% after cycle II, and increasing to 80.42% after cycle III. This research recommends that the use of loose-parts and utilizing the surrounding environment based on STEAM learning can be implemented in kindergarten institutions.